Desarrollo de un sistema web progresivo para la gestión de la información del botiquín La Josefina aplicando analítica de datos en las ventas utilizando la metodología de desarrollo de software SCRUM. - Sarango Pinto, Joel Patricio (2023)
Progressive Web Systems have emerged as an outstanding alternative to improve the user experience, so giving a fast and reliable navigation, especially in environments with limited network connections. This project is focused on the specific case of La Josefina drugstore which is located in Guasaganda rural parish, La Josefina precinct, La Maná canton. The drugstore offers services to sale generic and commercial medicines for all kinds of illnesses. However, its management and control have been carried out manually. This fact has resulted in various inconveniences and operational difficulties. The objective is to develop a Progressive Web System that improves sales and information management in La Josefina drugstore with the purpose of supporting decision-making through data analysis. To achieve the goal, the SCRUM methodology was applied, consisting of five phases: starting, planning and estimation, implementation, review and retrospective, and launching. The research methodology added the collection of data through surveys and interviews applied to the owner of the drugstore, which allowed obtaining the initial requirements for the development of the Web System; as a result a Progressive Web System was developed by using technologies such as JavaScript, CSS, PHP, and POWER BI for data analysis; along with the Bootstrap framework for the visual interface. The use of case diagrams have been implemented to define the interactions between users and the system. In addition, an entity-relationship model has been carried out for the selection and analysis of requirements. The implementation of the Progressive Web System through the SCRUM methodology has demonstrated to be an effective solution to improve sales management and control of information in La Josefina drugstore, so optimizing its operation and benefiting for both administrators and customers.